2000
DOI: 10.1111/j.1572-0241.2000.03348.x
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Low-Grade Dysplasia in Barrett's Esophagus and Its Implications for Disease Progression

Abstract: A high degree of interobserver variability is seen in the histological diagnosis of Barrett's esophagus-related LGD. Although the number of observations is low, a consensus diagnosis of LGD among GI pathologists suggests an increased risk of progression from LGD to HGD or carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(131 citation statements)
references
References 16 publications
5
119
0
7
Order By: Relevance
“…Previous studies have shown that p53 overexpression is associated with an increased risk of neoplastic progression in non-dysplastic BO and BO with LGD. The results of these studies are in line with the results of our study 12 13 16 17 18 34…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that p53 overexpression is associated with an increased risk of neoplastic progression in non-dysplastic BO and BO with LGD. The results of these studies are in line with the results of our study 12 13 16 17 18 34…”
Section: Discussionsupporting
confidence: 91%
“…However, histological diagnosis of LGD is subject to sample error and considerable interobserver variation, mainly because features of dysplasia may overlap with features of non-neoplastic regenerative changes 11. Although the predictive value of LGD increases with consensus of multiple pathologists, still one-third of patients with BO are diagnosed with LGD during surveillance, while the 10-year cumulative incidence of neoplastic progression is only around 15% in this subgroup 12 13. Use of biomarkers in addition to histological assessment may improve risk stratification for these patients, whereby more stringent surveillance is applied to individuals at high risk for neoplastic progression, while surveillance intervals are prolonged in those at low risk.…”
Section: Introductionmentioning
confidence: 99%
“…This was consistent with other studies 35–41. It is likely that an even better accuracy of risk prediction may be achieved by a consensus LGD diagnosis of more than one pathologist 37 40. In addition, the extent of the spread of LGD has been suggested to be another significant risk factor for the development of OAC 42…”
Section: Discussionmentioning
confidence: 99%
“…Most previously reported κ values range from 0.14 to 0.32, which can be classified as poor to fair agreement 10 12 21–24. Only a minority of studies reported moderate to good agreements between GI pathologists with a special interest in BO, with κ scores ranging from 0.48 to 0.69 11 13 25 26.…”
Section: Introductionmentioning
confidence: 99%